KARAKTERISTIK DAN FENOMENA PERUBAHAN KONSENTRASI OKSIGEN DAN NITROGEN DI UDARA DENGAN PROSES LASER-INDUCED BREAKDOWN SPECTROSCOPY (LIBS) - Suyanto, Hery (BULETIN FISIKA, 2013)
Characteristics and phenomena of hydrogen, oxygen and nitrogen in the air were investigated by Laser- Induced Breakdown Spectroscopy (LIBS). Neutral atomic spectra emission of hydrogen (H I), oxygen (O I) and nitrogen (N I) were analyzed by spectrometer with CCD 14.336 pixel, 200 – 980 nm, resolution of 0.1 nm and delay time detection was set 0 till 4 µs after  100 mJ of laser radiation. The optimum condition for detecting these elements when the delay time detection was between 0.05 – 1 ?s. The data of these elements show the intensity more than 150 a.u, the S/B above of 10 and the FWHM lower than 0.7. The air composition (%), however, was changed compare to the normal condition. Nitrogen was lower than oxygen  (N = 39 %, O = 55 %, H = 5 % and 1 % for others gas) .